2023
DOI: 10.1371/journal.pone.0286597
|View full text |Cite
|
Sign up to set email alerts
|

Was retrospective change measurement conducted with Covid-19 containment inconsistent? Comparing prospective and retrospective change measures using data from a national survey on substance use and addictive behaviors

Abstract: Single-measurement-point data collection to assess change has increased with studies assessing the impact of the Covid-19 pandemic and of its containment, despite evidence of its lack of validity. Retrospective change is not equivalent to change in repeated self-reported measures giving raise to questions about the validity of the former. This paper purports to investigate inconsistencies between change measures by confronting retrospective change to information from longitudinally self-reported measures from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition retrospective studies are exposed to recall bias (Dupuis et al 2023), but previous literature showed that recall is accurate regarding antidepressant use in pregnancy (Newport et al 2008). Even when people do not remember the exact brand name, they are able to state that they used antidepressants or psychotropic medication (van Gelder et al 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…In addition retrospective studies are exposed to recall bias (Dupuis et al 2023), but previous literature showed that recall is accurate regarding antidepressant use in pregnancy (Newport et al 2008). Even when people do not remember the exact brand name, they are able to state that they used antidepressants or psychotropic medication (van Gelder et al 2013).…”
Section: Limitationsmentioning
confidence: 99%